Colonization and damages of Ailanthus altissima (Mill.) Swingle on archaeological structures: Evidence from the Aurelian Walls in Rome (Italy). (September 2020) - Trotta, G.; Savo, V.; Cicinelli, E.; Carboni, M.; Caneva, G.
Abstract: Ailanthus altissima is an extremely aggressive and globally invasive species. This tree has ideal growing conditions in ruderal areas, and is difficult to manage, as cutting is a trigger for the sprouting of new suckers. Despite the wide literature on the negative impacts of this species, measurements of its interaction with archaeological monuments are lacking. We analyzed its colonization behavior and the caused damages along the Aurelian Walls in Rome, which resulted in detachments, crackings and deformation. Our results highlighted the rapid growth potential and wide distribution of this tree in the site (48 nuclei with 578 stems, mainly root suckers, along 7.1 km of 12.5 total length). Our study also provides a quantitative assessment of the damaging potential of A. altissima, as, in 16 out of 48 nuclei, we detected visible damage to the walls, which were likely due to both mechanical and chemical interactions through acidic exudates. The damages correlated significantly with plant size but not with plant distance from the walls, likely due to the wide lateral spread of the roots. This work highlighted the need to monitor and contain A. altissima, but also offers a general approach for the assessment of risks to monuments by higher plants. Graphical abstract: Image 1 Highlights: Ailanthus altissima is an invasive species often growing in archaeological sites. A. altissima can damage structures through mechanical and chemical action. We analyze the growth and spreading of this species along the Aurelian Walls (Rome). We analyze and quantify the damages it induces on these walls defining a risk map. We give a methodological contribution in the valuation of damage risk due to plants.